Naturalization as a Colonial Tool for Entrenching French Domination in Algeria (1830-1962) - Mimouna, Abed (Journal of Ecohumanism, 2025)
France’s Algerian naturalization policy (1830-1962) strategically reshaped demographics to reinforce colonial control. Selective laws (1865,1889) naturalized Europeans (especially Spaniards/Italians) while the Crémieux Decree (1870) collectively enfranchised Jews, contrasting sharply with Muslim marginalization under the Indigenous Code. This discriminatory system exposed colonial hypocrisy, using citizenship to establish racial hierarchies - culminating in Vichy’s 1940 revocation of Jewish rights. The policy’s legacy includes post-independence Jewish emigration and enduring social fractures, revealing naturalization as an instrument of division rather than unity in colonial Algeria.